Water quality assessment in selected areas of Boac River, Boac, Marinduque using allium test - Relles, Precious R. 4 0 16; 5 (2006)
ABSTRACT: Allium test was used to test if the tailing spill of Marcopper Mining Corporation which occurred to Boac River on March 24, 1996, has still significant effects to biological systems along the area. Medium sized, one year old stocked onion (Allium aggregatum) was used as a test specimen. Three sampling stations were established. Monthly samplinbg was done once a month from September to November 2005. Onions were germinated into tap water as acontrol and in water samples obtained from the study site and were observed for its macroscopic parameters. Number, length, form and color of roots and leaves were observed and recorded for its macroscopic analysis. Mitotic index, the presence of chromosonal aberrations were also computed for the microscopic analysis. One-way Analysis of Variance (ANOVA) was used for the statistical analysis using SPSS ver. 11.0. It was found out that control and experimental groups have morphological differences. It was also found out that there is a significant difference between the control and experimental groups in terms of length of leaves, length of roots, number of leaves and number of roots. Among the root cells grown in experimental group chromosomal aberrations such as sticky metaphase, c-mitosis, lagging chromosome, disturbed anaphase, disturbed metaphase and precocious chromosome were found. Moreover, it was found out that control group had the greatest mitotic index with an average of 70 and station three had the least mitotic index having an average of 18 in three months of sampling. In addition, station three had the greatest percent chromosomal aberration having an average of 38% and control had the least percent chromosomal aberration with an average of 2% in three months of sampling.
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2006.
Keywords: 2 -- 0; 6; 20; 20; 2